2019
DOI: 10.1111/bcpt.13245
|View full text |Cite
|
Sign up to set email alerts
|

Cefoperazone/sulbactam therapeutic drug monitoring in patients with liver cirrhosis: Potential factors affecting the pharmacokinetic/pharmacodynamic target attainment

Abstract: Objectives Cefoperazone/sulbactam trough concentration (Cmin) varies widely in cirrhotic patients. The objective of this study was to describe the characteristics of Cmin and to identify factors associated with the pharmacokinetic/pharmacodynamic (PK/PD) target attainment of cefoperazone/sulbactam in cirrhotic patients. Methods Data were collected retrospectively from cirrhotic patients who received cefoperazone/sulbactam treatment. The Cmin was measured using a validated liquid chromatography‐tandem mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…This is because tigecycline can play an antibacterial role by binding to the 30S subunit of bacterial ribosome and inhibiting bacterial protein synthesis [ 19 ], and cefoperazone can exert its antibacterial effect by inhibiting bacterial cell wall synthesis. Although sulbactam sodium itself has no antibacterial effect, it has an irreversible inhibitory effect on the production of β -lactamase by gram-negative bacilli, reducing its effect on the efficacy of cephalosporin antibiotics [ 20 ]. In general, the three-drug components can exert synergistic effects through different pathways to better control intracranial infection.…”
Section: Discussionmentioning
confidence: 99%
“…This is because tigecycline can play an antibacterial role by binding to the 30S subunit of bacterial ribosome and inhibiting bacterial protein synthesis [ 19 ], and cefoperazone can exert its antibacterial effect by inhibiting bacterial cell wall synthesis. Although sulbactam sodium itself has no antibacterial effect, it has an irreversible inhibitory effect on the production of β -lactamase by gram-negative bacilli, reducing its effect on the efficacy of cephalosporin antibiotics [ 20 ]. In general, the three-drug components can exert synergistic effects through different pathways to better control intracranial infection.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that sulbactam may intensify cefoperazone's effect on coagulation function [7]. A study on the PK/PD of cefoperazone/sulbactam in cirrhotic patients showed that the total clearance of cefoperazone was often decreased in cirrhotic patients [10], which would theoretically exacerbate vitamin K1 de ciency. Based on this pathogenic mechanism, vitamin K1 supplementation has been suggested as a resolution [18].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cirrhosis face an infection rate of 32-34%. Cefoperazone/sulbactam is recommended as the initial empirical treatment regimen for cirrhotic patients with infections [9][10]. However, the risk of coagulopathy may be underestimated.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a therapeutic drug monitoring study of cefoperazone/sulbactam, also a highly protein bound drug with cefoperazone primarily excreted through bile and 20–30% renal excretion, conducted in 70 cirrhotic patients has also observed that varied serum total bilirubin levels exerted differential effects on drug clearance. Specifically, lower trough concentration ( C min ) of cefoperazone was observed in patients with bilirubin levels at both lower and higher extremes (≤ 26.15 μmol/L and > 99.15 μmol/L), while patients with mid-range bilirubin levels (26.15–99.15 μmol/L) were more likely to achieve the pharmacokinetic/pharmacodynamic target [ 16 ]. It might be due to patients with normal bilirubin levels tend to have no or only mild hepatic dysfunction, whereas excessively elevated serum bilirubin may cause a greater proportion of unbound drug concentration through competitive binding to plasma albumin with highly protein bound drugs [ 17 ].…”
Section: Discussionmentioning
confidence: 99%